Low-Temperature Adaptation of the Snow Alga Chlamydomonas nivalis Is Associated With the Photosynthetic System Regulatory Process - Zheng, Yanli; Xue, Chunling; Chen, Hui; He, Chenliu; Wang, Qiang (Frontiers in Microbiology, 2020)
The alga Chlamydomonas nivalis thrives in polar snow fields and on high-altitude mountain tops, and contributes significantly on primary production in the polar regions; however, the mechanisms underlying this adaptation to low temperatures are unknown. Here, we compared the growth, photosynthetic activity, membrane lipid peroxidation, and antioxidant activity of C. nivalis with those of the model alga C. reinhardtii, under grow temperature and low temperatures. C. nivalis maintained its photosynthetic activity in these conditions by reducing the light-harvesting ability of photosystem II and enhancing the cyclic electron transfer around photosystem I, both of which limited damage to the photosystem from excess light energy and resulted in ATP production, supporting cellular growth and other physiological processes. Furthermore, the increased cyclic electron transfer rate, carotenoid content, and antioxidant enzyme activities jointly regulated the reactive oxygen species levels in C. nivalis, enabling recovery from excess excitation energy and reduced photooxidative damage to the cell. Therefore, we propose a model in which adaptive mechanisms related to photosynthetic regulation promote the survival and even blooming of C. nivalis under polar environment, suggesting that C. nivalis can provide organic carbon sources as an important primary producer for other surrounding life in the polar regions for maintaining ecosystem.